Persepsi Umat Katolik terhadap Kualitas Pendidikan Sekolah Katolik di Kevikepan Yogyakarta Barat dan Kevikepan Yogyakarta Timur - Ayu Widiastuti, Fransiska Lyra; Lintang Natalie, Maria Gratia; Agatha, Aurelia Christy; Maharani, Gabriella (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Perception is a viewpoint formed by individuals through the processing of information and experiences received via sensory processes. In this process, individuals provide interpretation and evaluation of certain stimuli or objects. This study aims to analyze the perceptions of Catholic communities regarding the quality of Catholic school education in the Yogyakarta Vicariate. The research employed a qualitative method with a realist approach. Data collection was conducted through a combination of Focus Group Discussions (FGDs) and a survey technique using Google Forms distributed via WhatsApp groups from June to August 2023. The research subjects were members of the Catholic community in 23 parishes of the Western Yogyakarta Vicariate and 25 parishes of the Eastern Yogyakarta Vicariate. Participants involved in the parish FGDs had experiences or engagement with Catholic school education, such as parents, students, teachers or educators, and school staff within both vicariates. The subjects participated in FGDs using several structured question instruments, and the results of these discussions were recorded in Google Forms. The findings were analyzed using a thematic analysis technique, revealing that Catholics in the Yogyakarta Vicariate have a positive perception of Catholic schools. However, the study also found a discrepancy between this positive perception and the actual data on new student admissions, which have declined in several Catholic schools.AbstrakPersepsi adalah pandangan yang dibentuk oleh individu melalui pengolahan informasi dan pengalaman yang diterima melalui proses penginderaan. Dalam proses ini, individu memberikan interpretasi dan penilaian terhadap stimulus atau objek tertentu. Penelitian ini bertujuan untuk menganalisis gambaran persepsi umat katolik terhadap kualitas pendidikan sekolah katolik di Kevikepan Yogyakarta. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan realis. Pengumpulan data dalam penelitian ini dilakukan dengan kombinasi Focus Group Discussion (FGD) dengan teknik survei melalui google form yang disebarkan ke WhatsApp Group dari bulan Juni hingga Agustus 2023. Subjek dalam penelitian ini adalah umat katolik yang berada di paroki wilayah Kevikepan Yogyakarta Barat sebanyak 23 paroki dan Kevikepan Yogyakarta Timur sebanyak 25 paroki. Umat katolik yang terlibat dalam FGD di paroki memiliki pengalaman atau terlibat dengan pendidikan sekolah katolik, seperti orang tua, murid, guru atau tenaga pendidik, hingga karyawan sekolah di Kevikepan Yogyakarta Barat dan Kevikepan Yogyakarta Timur. Subjek melakukan FGD menggunakan beberapa instrumen pertanyaan yang telah disusun, lalu hasil FGD tersebut dinotulensikan ke dalam google form. Hasil penelitian dianalisis dengan teknik tematik dan ditemukan bahwa umat katolik di Kevikepan Yogyakarta memiliki persepsi yang positif terhadap sekolah katolik. Hasil persepsi tersebut juga ditemukan ketidakselarasan antara persepsi positif umat katolik dengan kenyataan data penerimaan siswa baru yang mengalami penurunan di beberapa sekolah katolik.